Bacterial and viral infections and related inflammatory responses in chronic obstructive pulmonary disease - Silvestro Ennio D’Anna; Mauro Maniscalco; Francesco Cappello; Mauro Carone; Andrea Motta; Bruno Balbi; Fabio L. M. Ricciardolo; Gaetano Caramori; Antonino Di Stefano (Annals of Medicine, 2021)
AbstractIn chronic obstructive pulmonary disease (COPD) patients, bacterial and viral infections play a relevant role in worsening lung function and, therefore, favour disease progression. The inflammatory response to lung infections may become a specific indication of the bacterial and viral infections. We here review data on the bacterial–viral infections and related airways and lung parenchyma inflammation in stable and exacerbated COPD, focussing our attention on the prevalent molecular pathways in these different clinical conditions. The roles of macrophages, autophagy and NETosis are also briefly discussed in the context of lung infections in COPD. Controlling their combined response may restore a balanced lung homeostasis, reducing the risk of lung function decline.KEY MESSAGEBacteria and viruses can influence the responses of the innate and adaptive immune system in the lung of chronic obstructive pulmonary disease (COPD) patients.The relationship between viruses and bacterial colonization, and the consequences of the imbalance of these components can modulate the inflammatory state of the COPD lung.The complex actions involving immune trigger cells, which activate innate and cell-mediated inflammatory responses, could be responsible for the clinical consequences of irreversible airflow limitation, lung remodelling and emphysema in COPD patients.